Uji Aktivitas Antibakteri Ekstrak Etanol Daun Kemangi (Ocimum sanctum L.) Terhadap Pertumbuhan Bakteri Escherichia coli dan Staphylococcus aureus - Siti Khotimah, Maria Angelina, Masnur Turnip, (Jurnal Protobiont, 2015)
Escherichia coli and Staphylococcus aureus are pathogenic bacteria that can cause intestinal and skin infections. One of the potential medicinal plants that is active against bacteria is basil leaves (Ocimum sanctum). This research aims to examine the antibacterial activity of ethanol extracts of basil leaves againstthe growth of E. coli and S. aureus. The Research was conducted from September to December 2014. The ethanol extracts of basil leaves in this study used a concentration of 20%, 40%, 60%, 80%, 100%, and Thiamfenicol as a positive control. The antibacterial activity test to observe inhibition zone was done through the disc diffusion method. The results showed that the extracts of basil leaves were bacteriostatic. In this research, the highest inhibition zone occurred at a concentrations of 100%, while the optimum treatment in inhibiting the growth of E. coli and S. aureus was the concentration of 80%. Based on results of the phytochemical test, the ethanol extract of O. sanctum had a secondary metabolite compounds i.e. flavonoid, tannin, and essential oil that act as antibacterial. The Anova statistical results showed a significant difference in the diameters of the inhibition zone of the treatment of extracts with positive control.